2001
DOI: 10.1081/sei-100102697
|View full text |Cite
|
Sign up to set email alerts
|

Selective Recovery of Gold From Acidic Solutions Using Resins With Methylenediphosphonate and Carboxymethylphosphonate Ligands

Abstract: The polymeric resins with methylenediphosphonate and carboxymethylphosphonate ligands in the ethyl ester form have been synthesized, characterized and used in the removal of Au(III) from hydrochloric acid solutions. It has been found that they are able to adsorb as much as 130±166 mg Auag of the resin at high concentration of the external solutions. At low concentrations af®nity of resins towards gold is very good and the obtained distribution coef®cient logarithm is in the range of 4.0±4.4 for the 1610 À 4 M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…This stage was completed within about 5 min for IIP 4-VP-EGDMA and 40 min for the other two imprinted polymers. The observed faster uptake of Au(III) onto the IIP 4-VP-EGDMA compared to the other two IIPs could be due to its larger surface area and porous structure making the functional groups easily accessible to Au (III) (Trochimczuk 2001), which is in agreement with findings regarding the surface area and pore size discussed earlier (see Table S1). After attaining equilibrium (after 5 and 40 min) in the second step, there was no further increase in the Au(III) uptake owing to the occupation of all adsorption sites by the adsorbate ion.…”
Section: Effect Of Phsupporting
confidence: 90%
See 1 more Smart Citation
“…This stage was completed within about 5 min for IIP 4-VP-EGDMA and 40 min for the other two imprinted polymers. The observed faster uptake of Au(III) onto the IIP 4-VP-EGDMA compared to the other two IIPs could be due to its larger surface area and porous structure making the functional groups easily accessible to Au (III) (Trochimczuk 2001), which is in agreement with findings regarding the surface area and pore size discussed earlier (see Table S1). After attaining equilibrium (after 5 and 40 min) in the second step, there was no further increase in the Au(III) uptake owing to the occupation of all adsorption sites by the adsorbate ion.…”
Section: Effect Of Phsupporting
confidence: 90%
“…The high adsorption selectivity of the IIPs to gold ion compared to base metal ions at this pH can be attributed to several factors. The first factor could be the geometry of the complex anions in which gold (III) forms a square planar complex with the chloride anions (Trochimczuk 2001). The other base metal ions form tetrahedral or octahedral complexes resulting in different interactions with the IIPs.…”
Section: Selectivity Studies Of the Imprinted Polymers For Au(iii) Ve...mentioning
confidence: 99%
“…Carbon adsorbents were particularly very useful for recovery of gold from thiourea [30] and thiocyanate [31] solutions obtained in the leaching processes. Resins bearing amnioguanidyl ligands have revealed significant gold sorption from both acidic and alkali solution: 68 and 23 mg/g, respectively [35]. The investigated resins could be used in many cycles of sorption -desorption of AuCl 4 À where acidic thiourea solution at an ambient temperature was applied for gold recovery.…”
Section: Sorption and Ion-exchangementioning
confidence: 99%
“…[12]. It has been reported that hydrometallurgical processes are predictable, -easily controllable, environmentally friendly, higher selectivity to metals in comparison with pyrometallurgical methods [13].…”
Section: Introductionmentioning
confidence: 99%